Konsep dan Implementasi Sukuk sebagai Alternatif Obligasi Syariah - Margaretha, Rotua; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
Sukuk is an Islamic financial instrument that serves as an alternative to conventional bonds. Unlike bonds, which are based on debt and interest (riba), sukuk is based on asset ownership and profit-sharing in accordance with Sharia principles. This study aims to analyze the concept of sukuk, compare it with conventional bonds, and evaluate its implementation in Indonesia and globally. The research method used is qualitative with a descriptive-analytical approach based on secondary data from journals, regulations, and Islamic capital market reports. The findings indicate that sukuk has significant potential in supporting the development of the Islamic economy, particularly with the growing demand for halal investments. However, challenges such as low public literacy, the need for stronger regulations, and competition with conventional bonds remain obstacles to sukuk’s growth. With government support and innovation in the Islamic finance sector, sukuk can become a more competitive and attractive investment instrument for investors.